Digital Forensic Investigation for Non-Volatile Memory Architecture by Hybrid Evaluation Based on ISO/IEC 27037:2012 and NIST SP800-86 Framework - Rizdqi Akbar Ramadhan; Panji Rachmat Setiawan; Dedy Hariyadi (UIR PRESS, 2022)
In the implementation of Digital Forensics, one of the derivatives of practice is the handling of Digital Evidence. Handling Digital Evidence requires important steps and procedures. Digital evidence is a source of artifacts in handling a digital-based crime case, one of which comes from digital storage. In this research, the author will design a framework for Digital Forensic investigations by simulating digital evidence in the form of a non-volatile architecture. The reference commonly used by researchers in previous articles is the National Institute of Justice (NIST). The framework is a reference and steps in the practice of acquiring digital evidence. The purpose of designing this framework is as a legal procedure that is specifically implemented in the practice of acquiring non-volatile digital evidence. In the design, the author conducted a literature study on the NIST SP 800-86 and ISO 27037:2012 standards and then combined them in a hybrid terminology. The output of this research is to combine the two standards to become framework as reference for handling and investigating Digital Forensic science.